2018
DOI: 10.1111/raq.12296
|View full text |Cite
|
Sign up to set email alerts
|

Generation, characterization, perniciousness, removal and reutilization of solids in aquaculture water: a review from the whole process perspective

Abstract: The generation of solids by aquaculture activities has led to many problems in animal welfare, environmental quality, water treatment effects and public health, such as gill and intestinal damage, water eutrophication, system components blockages and antibiotics transfers through the food chain to human; thus, effective solid wastes management is very important. The purpose of this review is to summarize the sources, characterization methods, harmfulness, removal technologies and reutilization of solids in aqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 203 publications
0
15
0
Order By: Relevance
“…For the photoautotrophic BFT water process, flocculation is a good methodology, as well as filtration or bio clarification (<30 µm) (Espinal & Matulić, 2019), and to separate particles, various systems are available (Cripps, 1995; Cripps & Bergheim, 2000; Dauda, Ajadi, Tola‐Fabunmi, & Akinwole, 2019; Goddard & Al‐Abri, 2019). Furthermore, a combination of processes could be used to recover distinct particle sizes, with stations for sedimentation, adhesion, and filtration (Fimbres‐Acedo, 2015), or to implement the first and second treatments (Bao et al., 2018), including a protein skimmer or adding innovative systems such as biological aerated filters (BAFs), a sludge filter and a bioreactor for solid nutrient conversion (Zhang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the photoautotrophic BFT water process, flocculation is a good methodology, as well as filtration or bio clarification (<30 µm) (Espinal & Matulić, 2019), and to separate particles, various systems are available (Cripps, 1995; Cripps & Bergheim, 2000; Dauda, Ajadi, Tola‐Fabunmi, & Akinwole, 2019; Goddard & Al‐Abri, 2019). Furthermore, a combination of processes could be used to recover distinct particle sizes, with stations for sedimentation, adhesion, and filtration (Fimbres‐Acedo, 2015), or to implement the first and second treatments (Bao et al., 2018), including a protein skimmer or adding innovative systems such as biological aerated filters (BAFs), a sludge filter and a bioreactor for solid nutrient conversion (Zhang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a combination of processes could be used to recover distinct particle sizes, with stations for sedimentation, adhesion, and filtration (Fimbres-Acedo, 2015), or to implement the first and second treatments (Bao et al, 2018), including a protein skimmer or adding innovative systems such as biological aerated filters (BAFs), a sludge filter and a bioreactor for solid nutrient conversion (Zhang et al, 2020).…”
Section: Water Quality and Nutrients In The Bftmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published meta‐analysis concluded that their use was efficacious in improving shrimp survival, specific growth rate, and feed conversion ratio (Toledo, Frizzo, Signorini, Bossier, & Arenal, ). Nor does it include specific discussion on biofloc technology, which may be considered a multi‐trophic variation in the area of probiotics (Ahmad, Rani, Verma, & Maqsood, ; Avnimelech, ; Bao, Zhu, Jin, & Ye, in press; Emerenciano, Martínez‐Córdova, Martínez‐Porchas, & Miranda‐Baeza, ; Kathia, del Carmen, Aida, Jorge, & Daniel, ; Martínez‐Córdova, Emerenciano, Miranda‐Baeza, & Martínez‐Porchas, ; Neori, Shpigel, & Guttman, ).…”
Section: Promising New and Future Anti‐pathogen Measuresmentioning
confidence: 99%
“…The generation of solids from aquaculture has generated serious problems, ranging from problems in animal welfare to negative effects on environmental quality and public health (Bao et al . 2019). Thus, several studies have been focused on the development of techniques for a good management of solids such as separation by physical methods (Boyd et al .…”
Section: State Of the Art Of Integrated Shrimp–plant Culturesmentioning
confidence: 99%